The clinical spectrum and immunopathological mechanisms underlying ZIKV-induced neurological manifestations - Filgueiras, Igor Salerno; Torrentes de Carvalho, Amanda; Cunha, Daniela Prado; Mathias da Fonseca, Dennyson Leandro; El Khawanky, Nadia; Freire, Paula Paccielli; Cabral-Miranda, Gustavo; Schimke, Lena F.; Camara, Niels Olsen Saraiva; Ochs, Hans D.; Peron, Jean Pierre Schatzmann; Cabral-Marques, Otávio; et al. (PLOS Neglected Tropical Diseases, 2021)
Since the 2015 to 2016 outbreak in America, Zika virus (ZIKV) infected almost 900,000 patients. This international public health emergency was mainly associated with a significant increase in the number of newborns with congenital microcephaly and abnormal neurologic development, known as congenital Zika syndrome (CZS). Furthermore, Guillain–Barré syndrome (GBS), a neuroimmune disorder of adults, has also been associated with ZIKV infection. Currently, the number of ZIKV-infected patients has decreased, and most of the cases recently reported present as a mild and self-limiting febrile illness. However, based on its natural history of a typical example of reemerging pathogen and the lack of specific therapeutic options against ZIKV infection, new outbreaks can occur worldwide, demanding the attention of researchers and government authorities. Here, we discuss the clinical spectrum and immunopathological mechanisms underlying ZIKV-induced neurological manifestations. Several studies have confirmed the tropism of ZIKV for neural progenitor stem cells by demonstrating the presence of ZIKV in the central nervous system (CNS) during fetal development, eliciting a deleterious inflammatory response that compromises neurogenesis and brain formation. Of note, while the neuropathology of CZS can be due to a direct viral neuropathic effect, adults may develop neuroimmune manifestations such as GBS due to poorly understood mechanisms. Antiganglioside autoantibodies have been detected in multiple patients with ZIKV infection–associated GBS, suggesting a molecular mimicry. However, further additional immunopathological mechanisms remain to be uncovered, paving the way for new therapeutic strategies.